Synthesis, characterization and biological activity of new symmetrical 1,3-benzoxazine compounds - Hassan, Chiya Othman (2017)
l,3-Benzoxazine compounds constitute an important class among a wide variety of heterocyclic compounds that have been explored for developing pharmaceutically important molecules, due to their interesting biological activities. It is well known, that 1,3-benzoxazines have antimicrobial activity, or the ability to inhibit the growth of microorganisms such as bacteria, fungi or protozoans. Therefore, in this work, a series of new symmetrical 1,3-benzoxazine derivatives have been synthesized to study their antibacterial and antifungal activities in comparison with the standard drugs streptomycin and nystatin respectively. The synthesis of a series of new 1,3-benzoxazine compounds was achieved in high yield in two steps. In the first step, 1,1'-bis(4-hydroxyphenyl)cyclohexane was prepared from phenol and cyclohexanone via Friedel-Craft reaction. Subsequently, the bisphenol was treated with a variety of primary amines; including aliphatic, aromatic and heteroaromatic, in the presence of formaldehyde to produce new symmetrical 1,3-benzoxazine derivatives. The structures of all the newly synthesized compounds (nine compounds: including eight unknown compounds and one known intermediate) have been elucidated and confirmed by TLC and spectroscopic methods such as FTIR, 1H NMR, 13C NMR, GCMS and CHNS analysis. Following that, the in vitro bioactivity (antibacterial and antifungal) evaluation were performed for all new symmetrical 1,3-benzoxazine derivatives and 1,1'-bis(4-hydroxyphenyl)cyclohexane (bisphenol-C) against a panel of human pathogenic microorganisms: two gram positive bacteria (Bacillus Subtitles B29, Staphylococcus aureus S276) and two gram negative bacteria (Pseudomonas aeruginosa ATCC 15442, Escherichia coli E266) were used for the antibacterial assay, while (Aspergillus brasilliensis ATCC 16404) was used for the antifungal assay. Furthermore, the investigation of antimicrobial screening data clearly evident that most of the newly synthesized compounds exhibited excellent to moderate antibacterial activity against tested microorganisms as compared to that of the standard drugs. Among the newly prepared compounds, compounds 3,4-dihydro-2H-1,3-benzoxazine containing 5-methylisoxazole group was more potent than standard streptomycin against all the tested bacteria strains as well as equally potent against the tested fungus compared to nystatin drug. In addition, compound 3,4-dihydro-2-H-1,3-benzoxazine containing 2-aminothiazole group demonstrated similar effect against all tested microorganisms as compared to the standard drug streptomycin. Generally, newly synthesized compounds were active towards all bacteria strains and showed greater activity than initial parent which showed significant activity. In brief, a series of the new symmetrical 1,3-benzoxazine compounds were synthesized successfully in high yield and investigated for their antimicrobial activities for above-mentioned assays. The results showed that a number of 1,3-benzoxazines assayed inhibition the growth of certain bacteria and fungi which may help for drug development in the future.